RELATIONSHIP BETWEEN BIOLOGICAL ASPECT OF LIFE WITH DEPRESSIVE DISORDERS IN THE ELDERLY AT THE SCHOOL OF ELDERLY - Anugrah Alifio; Yanti Harjono Hadiwiardjo; Nasihin Saud Irsyad; Ria Maria Theresa (Universitas Airlangga, 2025)
Introduction: Depressive disorders are one of the most common disorders throughout the world, with a prevalence reaching 5.7% in elders aged over 60 years. In the elderly, depressive disorders can make patients feel miserable, worsen medical conditions, and require a proper support system. Aims: This study aims to explore the relationship between physical activity, cognitive ability, and medical history with depressive disorders in the elderly population in Pondok Labu, South Jakarta, Indonesia. Methods: A cross-sectional quantitative approach was utilized, involving elderly participants from the School of Elderly RPTRA Pinang Pola. Data were gathered via questionnaires, and analyses included univariate and bivariate methods, with the chi-square test assessing relationships between variables. Results: Among the 34 participants, 88.2% showed non-concerning levels of depression, while 11.8% exhibited light depression. Physical activity levels of intensity were light for 11.8%, moderate for 64.7%, and high for 22.3% of participants. Cognitive assessments indicated that 2.9% were below average, 94.1% were normal, and 2.9% were above average cognitive ability. Regarding medical history, 61.8% had up to two diseases, while 38.2% had more than two diseases. Bivariate analyses revealed no significant relationships between depression levels and physical activity (p=0.551), cognitive ability (p=0.118), or medical history (p=0.627). Conclusion: These findings suggest that depression may be influenced by factors beyond those studied here, highlighting the need for broader research on depression determinants in the elderly such as the level of loneliness and the function of family and friends in the elder’s environment.